KREDIT USAHA MIKRO PT. BANK MANDIRI (PERSERO) TBK DAN PENDAPATAN NASABAH - Adi Suroso, Rusmini. Elfreda Aplonia Lau. (EKONOMIA, 2015)
Based on the above, the headline writer formulated the problem is whether the provision of micro credit at PT. Bank Mandiri can increase customer revenue growth ?Basic theory used in the preparation of this skrips is management accounting with a focus on micro credit. The hypothesis of research into the formulation of the problem and the basic theory used is the provision of micro credit at PT. Bank Mandiri (Persero) Tbk can increase customer revenue growth.Analyzer used in this research is the analysis growth ratio is a simple formulation ((present-past) / past) x 100. Data collection techniques used is a field research through interviews between researcher and respondent or related parties, and with a literature study using secondary data from various literature related to the research as supporting the completion of this thesis.The results showed that administration of Micro Credit PT. Bank Mandiri bring a positive influence and can increase customer revenue. Based on the description of the results of research and discussion, the authors conclude that the provision of Micro Credit PT.Bank Mandiri can increase customer revenue growth. With loans obtained customers are expected to be used as well as possible to increase customer revenue